Impact of different production systems on the slaughter performance and meat quality of gayal (Bos frontalis) - Zhi, Li; Li, Qing; Wang, Zibei; Zhang, Meng; He, Shichun; Zhang, Hao; Dai, Sifan; Zhang, Lijuan; Zhao, Shusheng; Jiang, Feng; Wang, Lixing; He, Sheng; et al. (Frontiers in Veterinary Science, 2025)
ObjectiveThe aim of this study was to evaluate the influence of different production systems, including low-altitude indoor feeding, high-altitude indoor feeding, and high-altitude grazing, on the slaughter performance and meat quality of gayals.MethodsWe slaughtered 15 male gayals (five from each of three feedlots) that were randomly selected, with similar body weights within each feedlot. The gayals were raised under different production systems: indoor feeding at 1,325 m (TC, Tengchong feedlot; n = 5), indoor feeding at 2,240 m (FHS, Fenghuangshan feedlot; n = 5), and grazing at an altitude of 2,600 m (JMD, Jiumudang alpine pasture; n = 5). Gayals were slaughtered to evaluate slaughter performance, and the left longissimus dorsi (LD) and biceps femoris (BF) muscles were collected for meat quality analyses (pH45min, L45min*, a45min*, b45min*, muscle fiber diameter, water loss rate, shear force), chemical composition (moisture, crude protein, ether extract, cholesterol), amino acid composition, and fatty acid profile.ResultsThe results indicated that compared with the other two groups, the TC group exhibited significantly greater slaughter performance, including dressing percentage, lean meat percentage, and meat: bone ratio (p < 0.05). The TC group also showed higher levels of monounsaturated fatty acids (MUFA; especially C16:1 and C18:1 c9), essential amino acids (EAA), n-6:n-3 polyunsaturated fatty acids (PUFA) ratio, and thrombogenic index (TI), but lower cholesterol content (p < 0.05). In contrast, compared with the TC group, the JMD group had higher contents of PUFAs (including C18:3n3, C20:5n3, C22:5n3, and C22:6n3), a lower n-6:n-3 PUFA ratio, and a lower TI, with the TI decreased by 29.35% in LD muscle (p < 0.05). Additionally, the JMD group had higher contents of sweet amino acids in the LD muscle and umami amino acids in the BF muscle (p < 0.05). The slaughter performance and meat quality of the FHS group were intermediate between the TC and JMD groups, with closer alignment to the JMD group.ConclusionLow-altitude indoor-fed gayals demonstrated superior slaughter performance and higher beef yield, whereas high-altitude grazed gayals produced beef with a more favorable fatty acid profile and enhanced flavor-related amino acids, despite exhibiting lower productivity. High-altitude indoor-fed gayals exhibited slaughter performance and meat quality indicators that were intermediate between the two systems.